2019
DOI: 10.3390/info10100301
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Age and Subjective Well-Being: Towards Personalized Persuasive Health Interventions

Abstract: (1) Background: Subjective well-being (SWB) is an individual’s judgment about their overall well-being. Research has shown that high subjective well-being contributes to overall health. SWB consists of both Affective and Cognitive dimensions. Existing studies on SWB are limited in two major ways: first, they focused mainly on the Affective dimension. Second, most existing studies are focused on individuals from the Western and Asian nations; (2) Methods: To resolve these weaknesses and contribute to research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…Moreover, educational institutions should provide a wide space for students to become creative both in academic and non-academic fields via intracampus organizations that directly support social relations (Undip Chancellor Regulation Number 4, 2014). In contrast, late adults tend to perceive psychological well-being and life satisfaction through activities like spiritual values enhancements (Abdullahi et al, 2019).…”
Section: Ordinalmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, educational institutions should provide a wide space for students to become creative both in academic and non-academic fields via intracampus organizations that directly support social relations (Undip Chancellor Regulation Number 4, 2014). In contrast, late adults tend to perceive psychological well-being and life satisfaction through activities like spiritual values enhancements (Abdullahi et al, 2019).…”
Section: Ordinalmentioning
confidence: 97%
“…In college students, the age influence is apparent perhaps because they are young adult individuals who tend to actively perceive well-beings in social relationships, as shown through numerous organizational activities, habits to hangout, and relationships building (Abdullahi et al, 2019). Moreover, educational institutions should provide a wide space for students to become creative both in academic and non-academic fields via intracampus organizations that directly support social relations (Undip Chancellor Regulation Number 4, 2014).…”
Section: Ordinalmentioning
confidence: 99%
See 2 more Smart Citations
“…Research evidence revealed gender differences in subjective well-being. For instance, Abdullahi et al (2019) carried out a large-scale study of 732 respondents in Nigeria and presented a significant gender difference in subjective well-being. Findings of this study showed that females are more connected to emotional well-being, whereas males are more connected to satisfaction with life and social well-being.…”
Section: Gender and Subjective Well-beingmentioning
confidence: 99%